Modern Evaluative Practices in Teaching Romanian as a Foreign Language - Vintu, Victoria (Didactica Danubiensis, 2026)
This paper focuses on the analysis of pedagogical paradigm shifts in the field of language skills assessment, using the teaching of Romanian as a foreign language as a focal point. Strategies as formative assessment, which provides immediate and constructive feedback, and self-assessment – designed to stimulate the foreign student's autonomy in monitoring their own progress according to the levels of the Common European Framework of Reference for Languages are analyzed. The article describes the stages of the evaluation process, with emphasis on the importance of each component: descriptors, evaluation criteria, self-assessment. The research methods used are observation and case study. It shares efficient assessment practices applied in the groups of beginners. The modernization of assessment techniques in teaching Romanian as a foreign language represents a redefinition of the relationship between teacher and student; the teaching process becomes transparent, predictable, and focused on the real progress of the student. The article has significant academic and practical value, especially in the current context of globalization and the increase in the number of foreign students in the Republic of Moldova.